Association of the 11-year solar cycle with correlation and teleconnection structures in tropospheric circulation - Huth Radan; Stryhal Jan (Journal of Space Weather and Space Climate)
Analyzing spatial correlation structures and teleconnections in the 500 hPa heights of the Northern Hemisphere Extratropics in winter shows substantial differences between months with high and low solar activity. Patterns of spatial correlations of mid-tropospheric circulation differ between solar minima and maxima; the differences are geographically variable, particularly large and statistically significant in parts of the North Atlantic and North Pacific. Correlation structures of tropospheric circulation are significantly larger in solar maxima over parts of the North Atlantic. The geographical orientation of teleconnections is also associated with solar activity, the differences being most notable over the North Atlantic, North America, and the Arctic. The differences in teleconnections form a background for a response of modes of circulation variability and blocking anticyclones to solar activity, detected in previous studies. We detected no evidence of potential interference of responses to solar activity with quasi-biennial oscillation and volcanic eruptions; the interference with El Niño-Southern Oscillation is unlikely. The response to solar activity may be partly confused with the response to major sudden stratospheric warmings; however, sudden stratospheric warmings themselves may respond to the solar cycle.